2022
DOI: 10.26493/1855-3974.1955.1cd
|View full text |Cite
|
Sign up to set email alerts
|

Notes on weak-odd edge colorings of digraphs

Abstract: A weak-odd edge coloring of a general digraph D is a (not necessarily proper) coloring of its edges such that for each vertex v ∈ V (D) at least one color c satisfies the following conditions: if d − D (v) > 0 then c appears an odd number of times on the incoming edges at v; and if d + D (v) > 0 then c appears an odd number of times on the outgoing edges at v. The minimum number of colors sufficient for a weak-odd edge coloring of D is the weak-odd chromatic index, denoted χ ′ wo (D). It is known that χ ′ wo (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 7 publications
(8 reference statements)
0
7
0
Order By: Relevance
“…They believed that a descriptive characterization similar to graphs is impossible for all digraphs and they believed that deciding the exact value of χ ′ wo (D) is NP-hard. In [6], the authors showed a necessary and sufficient condition for digraphs to be weak-odd 2-edge colorable, and thus χ ′ wo (D) can be determined in polynomial time. When limit to 2 colors, use def(D) to denote the defect of D, the minimum number of vertices in D at which the condition ( − − → WO) is not satisfied.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…They believed that a descriptive characterization similar to graphs is impossible for all digraphs and they believed that deciding the exact value of χ ′ wo (D) is NP-hard. In [6], the authors showed a necessary and sufficient condition for digraphs to be weak-odd 2-edge colorable, and thus χ ′ wo (D) can be determined in polynomial time. When limit to 2 colors, use def(D) to denote the defect of D, the minimum number of vertices in D at which the condition ( − − → WO) is not satisfied.…”
Section: Introductionmentioning
confidence: 99%
“…When limit to 2 colors, use def(D) to denote the defect of D, the minimum number of vertices in D at which the condition ( − − → WO) is not satisfied. Hernández-Cruz, Petruevski, and Krekovski [6] proved that def(D) is related to the matching number of some graphs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations